A Review of Deciphering the Successes and Learning from the Failures in Preventive and Health Policies to Stop the Covid-19 Pandemic - Sandoval, A; Sandoval, A (Elsevier, 2021)
Since the onset of the COVID-19 pandemic, some countries have had successful experiences as well as failures. Countries have taken significant and different approaches to reducing the spread of COVID-19. This chapter states the soft method and herd immunity policy of some European countries (e.g., Sweden) in the early days of the epidemic, which failed. Most countries (e.g., Italy) that enacted a mandatory lockdown during the epidemic soon realized that this trend should not continue for longer periods because of side effects, namely social and economic troubles. Some other countries (e.g., Germany) imposed a social distancing of two meters in public places, which have been effective in reducing infection. Nowadays, reports indicate that some Asian countries have had more success than most European and American countries in taking containment measures. Hong Kong and Singapore are among the most successful countries in the world since the beginning of the pandemic, while the United States and Brazil are among the countries that have handled the development of the pandemic worst. Wearing a face mask in combination with social distancing is effective around 50% of the time. However, a complete combination of the following contention policies must be carried out by all countries, always considering the political, social, and above all, economic characteristics of each of them: (1) use face masks in public places, (2) keep suitable physical distancing, (3) extremely thorough hand hygiene, and (4) isolate all infected people. This should also include improving the ventilation in enclosed environments, designing safe routes in public and particular business locations, together with cleaning and disinfection activities. © 2021 Elsevier Inc. All rights reserved.
Keywords: COVID-19 pandemic; Herd immunity; Lockdown; Mask wearing; Preventive strategies; Social distancing